Search for the rare decay [lambda]+c→p[mu]+[mu]- - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Berninghoff, Daniel; Braun, Svende; De Cian, Michel; Comerma-Montells, Albert; Dordei, Francesca; Dziewiecki, Michal; Gerick, David; Grabowski, Jascha; Han, Xiaoxue; et al. (Physical review, 2018)
A search for the flavor-changing neutral-current decay Λ+c→pμ+μ− is reported using a data set corresponding to an integrated luminosity of 3.0 fb−1 collected by the LHCb Collaboration. No significant signal is observed outside of the dimuon mass regions around the ϕ and ω resonances, and an upper limit is placed on the branching fraction of B(Λ+c→pμ+μ−)<7.7(9.6)×10−8 at 90%(95%) confidence level. A significant signal is observed in the ω dimuon mass region for the first time.
Im Titel werden "Lambda" und "mu" als griechische Buchstaben dargestellt
Im Titel werden "+" und "-"hochgestellt, "c" tiefgestellt
The LHCb collaboration: R. Aaij, P. d'Argent, S. Bachmann, D. Berninghoff, S. Braun, A. Comerma-Montells, M. De Cian, F. Dordei, M. Dziewiecki, D. Gerick, J.P. Grabowski, X. Han, S. Hansmann-Menzemer, M. Kecke, B. Khanji, M. Kolpin, R. Kopecna, B. Leverington, J. Marks, D.S. Mitzel, S. Neubert, M. Neuner, T. Nikodem, A. Piucci, M. Stahl, S. Stemmle, J. van Tilburg, U. Uwer, A. Zhelezov [und weitere]
Gesehen am 28.05.2019